Management of organic soils to reduce soil organic carbon losses - Paul, Sonja (Burleigh Dodds Series in Agricultural Science, 2023)
Organic soils of intact peatlands store 1/4 of the global soil organic carbon (SOC). Despite being an important source of methane (CH4), they are climate coolers because they continuously accumulate new organic carbon. However, when these organic soils are drained for agriculture, the resulting aerobic conditions lead to fast decomposition of the peat and the release of carbon dioxide (CO2) and nitrous oxide (N2O), turning them into net greenhouse gas (GHG) sources. Reducing the environmental footprint of managing these soils requires a good understanding of the processes during drainage of formerly anoxic soil horizons and eventual subsequent rewetting. We describe changes in soil properties and carbon dynamics following drainage of peatlands and discuss management strategies to reduce carbon loss from drained peatlands by raising the water table to either restore the peatland ecosystem, or to cultivate water-tolerant crops. In addition to rewetting, engineering approaches with continuous management at deeper water tables are evaluated in terms of SOC loss.